The Pursuit of Happiness - The Impact of British Advertising on the Materialistic Aspirations of Polish Immigrants in the UK - Quandt, Piotr Bernard (2009)
The expansion of United Europe in May 2004 contributed into significant influx of Polish foreign labour to Great Britain, mainly for the reasons of lack of options in fulfilling their own needs and desires – determinates of happiness, in their home country. However afer a short period of time, initial claims related to the duration of stay, have changed, and the majority instead of planned short period of emigration decided to stay longer, sometimes even for life. This research investigates this trend in relation to the advertising on individual, social and cultural levels in Britain, as a medium often criticised for changing peoples materialistic aspirations, by assigning spectrum of significant meaning to promoted products. Verbatim text of ten qualitative interviews with Polish immigrants are interpreted within a theoretical framework based on socio-psychological aspects like the notion of empty self - self that’s bereaved family, tradition and cultural influence, as well as alienation and anxiety within a new social environment. It is therefore proposed that it is not advertising that is responsible for this change in immigrant’s values, but human need of replication of a collective patterns of preferences based on ‘class’ differentiation, as well as willingness to adopt to the new, ‘normative’ social image. In this context, advertising indeed plays an important part in immigrants’ life, however instead of influencing their materialistic aspirations, it only explains the social consumption norms that exist in the UK.